SAT0729-HPR Psychological profile of patients with fibromyalgia syndrome. (15th June 2017) - Xhaxho, D; Lauri, J; Lauri, MA; Soler, J Fleri; Borg, A; Mercieca, C
Abstract : Background: Fibromyalgia (FM) is a chronic non inflammatory condition characterized by pain and fatigue as well as physical and psychological symptoms. Management can be particularly challenging and a combination of pharmacological and non pharmacological treatments are recommended. Objectives: The aim was to study the level of anxiety and depression in fibromyalgia patients and whether these were associated with symptom severity, functional status, social or demographic factors. Methods: A cross sectional survey of 155 consecutive patients attending the nurse-led fibromyalgia clinic was carried out. Patients were diagnosed using the 2010 ACR diagnostic criteria. Demographic data, Widespread Pain Index (WPI), Symptom Severity Score (SSS), VAS pain and VAS fatigue were recorded. Patients filled in the self-administered questionnaires including the Revised fibromyalgia impact questionnaire (FIQR), Hospital Anxiety and Depression Scale (HADS). Patients were classified as suffering from high anxiety or depression if HADS was ≥11, moderate if 8–10 and low ≤7 for each scale respectively. Cross tabs and chi squared were used to study associations between anxiety and depression and social and demographic factors. Logistic regression analysis was performed to identify whether WPI, SSS, FIQR, VAS pain and VAS fatigue were predictors of severe anxiety and depression. Results: One hundred fifty five patients (92% female) participated in the survey. The average age was 50.3 years (SD 11.5) and mean duration of symptoms 13.4 years (SD 11.3). The mean HADS-A (anxiety) was 11.8 (SD 4.13), HADS-D (depression) 9.1 (SD 3.8) and FIQR 60.3 (SD 17.6). High levels of depression were reported by 31.5%, moderate 32.1% and low 30.3%. High levels of anxiety were reported by 60%, moderate 21.2% and low 13.3%. Both high levels of anxiety and depression were found in 25.2% of patients. SSS was the single best predictor for anxiety (p=0.001) while disease duration (p=0.01), SSS (p=0.02) and FIQR (0.04) predicted depression. VAS pain and VAS fatigue were not good predictors of severe anxiety and depression. When patients with high levels of anxiety and depression were compared with those with moderate and lower levels no association was found with age or social factors including occupation, marital status, level of education and family support. Conclusions: Both severe anxiety and depression were highly prevalent in our FM cohort, particularly anxiety. All FM patients need to be screened for anxiety and depression particularly those with high SSS and FIQR scores and longer disease duration. A psychiatrist and psychotherapist with a special interest in FM are essential members of the multidisciplinary team to ensure that anxiety and depression are addressed early prior to starting further interventions for FM. References: Jensen KB, Fransson P, Marcus HM, Williams SCR, Choy E, Mainguy Y, Gracely R, Ingvar M, Kosek E (2010) anxiety and depression in fibromyalgia are related to poor perception of health but not to pain sensitivity or cerebral processing of pain. Arthritis & Rheumatology Journal 62(11). Ugar M, Sarp U, Karaaslan O, Tanik N, Arik HO (2015) Health anxiety and depression in patients with fibromyalgia syndrome. Journal of Inernational Medical Research 45(3):679–685. Acknowledgements: NIL. Disclosure of Interest: None declared